OPERATIONAL PERFORMANCE OF PALABUHANRATU FISHING PORT SUKABUMI OF WEST JAVA - Sertia Simanjuntak; Alit Hindri Yani; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Palabuhanratu Fishing Port is one of the centers of fisheries activities which are currently in the stage of planning to upgrade the status of Ocean Fishing Port. Provision of good facilities and quality services is the most important thing in supporting these activities.However, the problems that exist in fishing ports have been the low level of operation and service of fishing ports caused by internal and external factors of the fishing port. This research was conducted to calculate the operational performance of the fishing port by observing operational activities and fishermen's satisfaction with port services. This research was carried out in May 2018 at the Palabuhanratu Fishing Port, Sukabumi Regency, West Java Province.The results of the analysis carried out showed that the operational performance of Palabuhanratu was included in the category of good enough with a value of 2.72.The achievement of this value is supported by the number of production and frequency of ship visits, each of which has 72.20% and 90.84% success rates, while for the provision of facilities and low service quality, with an average of 16%.This shows that further development of Palabuhanratu must pay more attention to the provision of facilities and quality of service. Keywords: Fisherman Satisfaction, Performance, Operational, Fishing Port